ЖИТТЄЗДАТНІСТЬ ПРИНЦИПІВ-ПРИПУЩЕНЬ БУХГАЛТЕРСЬКОГО ОБЛІКУ ДІЯЛЬНОСТІ НЕБАНКІВСЬКИХ ФІНАНСОВО-КРЕДИТНИХ УСТАНОВ (International Journal of Innovative Technologies in Economy, 2018)
The article reveals scientific approaches to the accounting principles system structure, which defines the leading role of the assumptions. The composition of the principles-assumptions of the accounting activities of non-bank financial and credit institutions (autonomy and going concern) is outlined and, the assessment of the principles viability according to the criteria of relevance, objectivity and feasibility is given. It is determined that these principles fully meet the criteria of objectivity and feasibility, and under the criterion of relevance, the principle of going concern is somewhat dubious, and the principle of autonomy is meaningless for non-bank financial institutions and needs to be replaced by the principle of a relevant reporting entity. This situation confirms the overall compliance of these principles with the criteria for viability, but requires the consideration of the conventions and information risks associated with the special aspects of the activities of non-bank financial and credit institutions.